CD4 depletion in SIV-infected macaques results in macrophage and microglia infection with rapid turnover of infected cells. - Luca Micci; Xavier Alvarez; Robin I Iriele; Alexandra M Ortiz; Emily S Ryan; Colleen S McGary; Claire Deleage; Brigitte B McAtee; Tianyu He; Cristian Apetrei; Kirk Easley; Savita Pahwa; et al. (PLoS Pathogens)
In rhesus macaques (RMs), experimental depletion of CD4+ T-cells prior to SIV infection results in higher viremia and emergence of CD4-independent SIV-envelopes. In this study we used the rhesus recombinant anti-CD4 antibody CD4R1 to deplete RM CD4+ T-cells prior to SIVmac251 infection and investigate the sources of the increased viral burden and the lifespan of productively infected cells. CD4-depleted animals showed (i) set-point viral load two-logs higher than controls; (ii) macrophages constituting 80% of all SIV vRNA+ cells in lymph node and mucosal tissues; (iii) substantial expansion of pro-inflammatory monocytes; (iv) aberrant activation and infection of microglial cells; and (v) lifespan of productively infected cells significantly longer in comparison to controls, but markedly shorter than previously estimated for macrophages. The net effect of CD4+ T-cell depletion is an inability to control SIV replication and a shift in the tropism of infected cells to macrophages, microglia, and, potentially, other CD4-low cells which all appear to have a shortened in vivo lifespan. We believe these findings have important implications for HIV eradication studies.